INFORMATION SYSTEM PROTOTYPE WEB-BASED HEALTH FOOD DELIVERY - S.Kom.,M.Pd, Arifudin; Baehaqi, Mudofar; Siswanto, Agus; Rosalina, Mia (Mestro: Jurnal Teknik Mesin dan Elektro, 2023)
The development of Industry 4.0 era makes today's technology more modern. With the development of technology, the use of Information Technology in business is increasing to help increase productivity, efficiency, and business profits. Epa Café & Resto is a business engaged in culinary. Epa Café Resto has problems such as still using a manual system, the customer must come to the restaurant to transact and the absence of digital promotion making it difficult to compete. The proposed solution to overcome the problem is to create an information system in the form of website delivery order. The Website is built using the waterfall method, while the programming language used is PHP and utilizes the code Igniter framework. Testing the system using blackbox testing method. The test results stated that the information system can work in accordance with the specifications and in accordance with user needs. The resulting information system can make it easier for customers to make transactions anywhere and anytime without having to come to the place. In addition, with the presence of this website, data processing will be more effective, efficient, and also transparent so that it can facilitate the process of sales transactions.